Medidas de espectroscopia Raman em cristais de DL-norvalina submetidos a altas pressões - Olivier, Lucas Saraiva Alves (2023)
It is known that amino acids are extremely important because they are the basic units that form proteins that are indispensable for life in general. Amino acids have a lot of versatility in their structures, being able to form polymorphs, bind with other amino acids to form dipeptides, and even with other molecules that can form salts, complexes, etc. This range of possibilities guarantees different properties that can be applied in the area of technology such as the pharmaceutical industry, applications in non-linear optics and electronic components. The studies of these materials subjected to extreme conditions of temperature and pressure are kept very hot, in order to determine the stability of the crystalline structure. In this work, the study is focused on Raman spectroscopy measurements under high pressures in DL-norvaline crystals, an amino acid that is important because it is similar to the amino acid valine and has several applications in drugs. According to the literature, DL-norvaline presents three polymorphic phases at low temperatures: β-form with C2/c space group and monoclinic crystallographic system, α-form with monoclinic P21/c space group and an X-form with undetermined structure. In this study, the measurement in the β-form was performed from ambient pressure up to 4.33 GPa, which observed some phase transitions that may be related to existing phases at low temperatures.